Shooting scene 330 - Lockwood, Victor; British Broadcasting Corporation. Television Service (Milton Keynes : Open University, 1977)
Shows the shooting process in production of film and motion pictures
Note: 1p.
Converted into VHS 1/2 in. and U-matic
Title from title screen
Film cameramen, John Baker, Fred Hamilton ; sound, Mike Turner, Ian Sansam ; film editor, Ran De Mattos ; executive producer, Micheal Philps
Narrator : Janet Woollacott
Keywords: Motion pictures -- Setting and scenery; Motion pictures -- Production and direction